BIRD FAUNA OF URBANIZED TERRITORIES OF SOUTH-WEST QAZAQSTAN (ON THE EXAMPLE OF QYZYLORDA CITY) (Experimental biology, 2024)
Biodiversity is a fundamental part of sustainable development, but it is threatened by numerous factors related to population growth. The rapid urbanization of the world has a profound impact on global biodiversity, and urbanization is considered one of the processes contributing to the homogenization of the world's biota. Currently, there is an increase in the anthropogenic load on the biodiversity of the urban environment in the arid conditions of the Kazakh part of the Aral Sea region. This contributes to the development of a number of negative processes (transformation of components of the natural environment, violation of the ecological, socio-economic situation). As a result, there is a need to study the response of biological resources to anthropogenic impact, as well as to climate changes observed in the region. There is an urgent need to conduct comprehensive research aimed at studying and evaluating the pace of changes in species richness and diversity in the structure of the fauna and flora of the region. One of the indicators of environmental transformation is considered to be the bird fauna, due to its sensitivity to any changes in nature. Quantitative accounting of avifauna can serve as a reliable method for analyzing the sometimes subtle shades of changes in the composition of the bird fauna. Currently, there is a rapid increase in the horizontal area and the number of floors of buildings in the vertical direction in Kyzylorda. This makes an adjustment to the comfortable existence of the avifauna. There are no data on monitoring the avifauna of the city of Kyzylorda in the available literature. Taking into account the above, the authors of the project have attempted to conduct year-round bird counts within Kyzylorda since 2019. This scientific research was initiated for the purpose of an interim analysis of the results of scientific work.
Keywords: Urban ecosystem; avifauna of urbanized territories; Kyzylorda; biological resources; anthropogenic load